2021
DOI: 10.1155/2021/3520034
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Ginsenoside Rg3 Alleviates Antithyroid Cancer Drug Vandetanib‐Induced QT Interval Prolongation

Abstract: Inhibition of human ether-a-go-go-related gene (hERG) potassium channel is responsible for acquired long QT syndromes, which leads to life-threatening cardiac arrhythmia. A multikinase inhibitor, vandetanib, prolongs the progression-free survival time in advanced medullary thyroid cancer. However, vandetanib has been reported to induce significant QT interval prolongation, which limits its clinical application. Some studies have showed that ginsenoside Rg3 decelerated hERG K(+) channel tail current deactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Ginsenoside Rg3, a tetracyclic triterpene saponin extracted from Red ginseng, has been shown to selectively inhibit tumor cell invasion and metastasis [ 115 ]. However, a study on the QT prolongation induced by the anti-thyroid cancer drug vandetanib showed that ginsenoside Rg3 combined with vandetanib could increase the inactivating current of hERG Kchannel, thereby reversing the QT prolongation [ 116 ].…”
Section: Natural Compounds That Attenuate Adverse Effects Of Chemothe...mentioning
confidence: 99%
“…Ginsenoside Rg3, a tetracyclic triterpene saponin extracted from Red ginseng, has been shown to selectively inhibit tumor cell invasion and metastasis [ 115 ]. However, a study on the QT prolongation induced by the anti-thyroid cancer drug vandetanib showed that ginsenoside Rg3 combined with vandetanib could increase the inactivating current of hERG Kchannel, thereby reversing the QT prolongation [ 116 ].…”
Section: Natural Compounds That Attenuate Adverse Effects Of Chemothe...mentioning
confidence: 99%
“…Western blot analysis was performed to detect the protein expression with the protocol as described previously [11]. Briefly, total protein was extracted by using RIPA lysis buffer containing protease inhibitors for 15~20 min from ventricular tissues of WKY, SHR, or human fibroblasts.…”
Section: Western Blottingmentioning
confidence: 99%
“…Meyer, possess a plethora of pharmacological properties 7 . Moreover, ginsenosides have been reported to confer anti‐tumour effects in a variety of cancers including gastrointestinal cancer, non‐small cell lung cancer, and thyroid cancer 8–10 . Ginsenoside Rh1 is one of the main bioactive compounds extracted from red ginseng, and recent investigations have suggested that Rh1 as a traditional medicine monomer is capable of exerting certain antitumor properties 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, ginsenosides have been reported to confer anti-tumour effects in a variety of cancers including gastrointestinal cancer, non-small cell lung cancer, and thyroid cancer. [8][9][10] Ginsenoside Rh1 is one of the main bioactive compounds extracted from red ginseng, and recent investigations have suggested that Rh1 as a traditional medicine monomer is capable of exerting certain antitumor properties. 11,12 What is more, ginsenoside Rh1 was previously associated with a blockade of cell migration and invasion in breast cancer and colorectal cancer.…”
mentioning
confidence: 99%